社会政治对于华文书业与出版业的影响 ：以上海书局业务转变为例 = The influence of social politics on Chinese bookstore and Chinese publishing industry : a case study of Shanghai book company - 朱婉齐 Choo, Wan Qi (2019)
本文主要以1925年创立于新加坡的上海书局为主要研究目标。上海书局在五四新文化运动后顺应东南亚华人的文化需求而生，以传播新文化知识为主要目的，填补东南亚新文化书刊匮乏局面。上海书局的业务版图曾涉及新马港印，从二战、新中国成立到东南亚各国反殖民独立的不同阶段中，其随着社会与国际政治局势做出相应的业务调整。新中国成立后，禁书令导致书源缺乏，上海书局联合多间书局开始了香江出品之路。其业务转变展现的是各个时代的社会文化面貌及文化生命力，战后印尼排华及新马各种华教政策的落实，导致上海书局面临转型、经营困境，甚至结业的命运。另一方面，上海书局的出版物亦随着时代与政局而改编，从以中国为本位的现代化教科书与香江出品，到马来亚化的教科书及书刊。语言上也从华语出版到多语出版，更顺应马来亚独立前夕的国语热出版了各类学习马来语的书刊。出版物的多样化与改编展现了新马华人认同转变的历程。This paper is focuses on Shanghai Book Company, founded in 1925 in Singapore. It was founded in response to the cultural demands of Southeast Asian Chinese after the May Fourth New Culture Movement. Its main purpose is the disseminating of the new cultural knowledge and fills the shortage of vernacular and new cultural books in Southeast Asia. The Shanghai Book Company branch has been established in Singapore, Malaysia, Hong Kong, and Indonesia. Shanghai Book Company had made the corresponding business adjustments with the social and international political situation. After the Founding of the new China, the British Colonial Government have promulgated a decree of the prohibition of importation on left-wing Chinese book, it led to the shortage of Chinese books supply. Shanghai Book Company cooperated with few Singapore Chinese bookstore to start the “Xiang Jiang Production”. The transformation of Shanghai Book Company has also shown the cultural vitality of the Singaporean social. The implementation of various Chinese education policies of Singapore, Malaysia, and Indonesia after World War II had caused Shanghai Bookstore some issues including the issue of transformation, operational dilemma and even termination of the business. The publications of the Shanghai Book Company have been adapted according to the social and political the situation, from the modern textbook with China consciousness, “Xiang Jiang production”, to the localization and Malayanization of books. It had also started to publish multilingual publications, such as English and science textbook which comply with Malaysian Education Policy. In the trend of anti-colonies, Shanghai Book Company has published various books of learning Malay. Therefore, the diversification and adaptation of publications have shown the identity transform of the Singaporean and Malaysian.